Estimating the parameters of Cowan’s M3 headway distribution for roundabout capacity analyses - Vasconcelos, Luís (2012)
Capacity models based on the gap acceptance theory are widely used in unsignalised intersections and roundabout capacity analysis. These models are based on the statistical distribution of major vehicle headways. In this field, Cowan’s M3 distribution is usually recognized as the most adequate, but the estimation of its parameters is not trivial. In this paper, the main estimation methods are reviewed and a new method (Simultaneous Numerical Estimation – SNE) is proposed. The SNE method was used to develop a calibrated relation between parameters, using field data collected in Portuguese roads and roundabouts. It was determined that the new formula improves capacity estimates, either in one-lane or in two-lane roundabouts. The paper also addresses the importance of each input variable and parameter in the resulting capacity model, through a sensitivity analyses.